2007
DOI: 10.1038/sj.ki.5002102
|View full text |Cite
|
Sign up to set email alerts
|

Normal distribution and medullary-to-cortical shift of Nestin-expressing cells in acute renal ischemia

Abstract: Nestin, a marker of multi-lineage stem and progenitor cells, is a member of intermediate filament family, which is expressed in neuroepithelial stem cells, several embryonic cell types, including mesonephric mesenchyme, endothelial cells of developing blood vessels, and in the adult kidney. We used Nestin-green fluorescent protein (GFP) transgenic mice to characterize its expression in normal and post-ischemic kidneys. Nestin-GFP-expressing cells were detected in large clusters within the papilla, along the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 26 publications
2
53
0
3
Order By: Relevance
“…Interestingly, nestin-expressing cells have been located around vasa rectae and, in certain experiments, can participate in angiogenesis, acquiring expression of Tie-2. 65 The observations that some epithelia express Tie genes 12,22,66 should lead to a careful search for these receptors on subsets of renal epithelia, using confocal microscopy and imaging of cilia. If such expression could be established, then it may help to explain some nonendothelial effects observed when angiopoietins are overexpressed.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Interestingly, nestin-expressing cells have been located around vasa rectae and, in certain experiments, can participate in angiogenesis, acquiring expression of Tie-2. 65 The observations that some epithelia express Tie genes 12,22,66 should lead to a careful search for these receptors on subsets of renal epithelia, using confocal microscopy and imaging of cilia. If such expression could be established, then it may help to explain some nonendothelial effects observed when angiopoietins are overexpressed.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Earlier studies described nestin as a marker of highly proliferative [36][37][38][39] and migrating cells. 37 In the kidney, a recent study showed nestin-positive cells migrating from the renal papilla to the cortex after ischemia/ reperfusion, 40 indicating a potential role of nestin also for renal cell migration. We found that nestin is a marker that promotes MC proliferation but not migration in vitro.…”
Section: Nestin In the Injured Glomerulus C Daniel Et Almentioning
confidence: 99%
“…20 Similarly, as in the rat, interstitial cells were markedly more abundant in the base of the papilla than in its tip (data not shown). The H2B-GFP mouse further allowed us to examine several potential markers of the interstitial LRCs, and, stimulated by recent findings, 19 we examined for the presence of nestin; as shown in Figure 7, B and C, we found that the interstitial LRCs were nestin positive.…”
Section: Characterization Of Papillary Lrcsmentioning
confidence: 99%
“…Patschan et al 19 reported a population of nestin-positive cells in the kidney papilla that migrates to other parts of the kidney after injury. Because papillary LRCs are present over the whole length of the papilla but proliferate in its upper region and their abundance in the papilla decreases with age, it suggests that the cells upwardly migrate to provide a steady supply of proliferating cells.…”
Section: Migration Of Papillary Cellsmentioning
confidence: 99%